Diversity of ecological functions of the insect families found in Citalahab Area of Mount Halimun Salak National Park (TNGHS) - Ruslan, Hasni; Rahmah, Alifia; Nurindri Y, Emilia; Faruq H, Johan; Nazak H, Abdimas (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2024)
The Citalahab area of ​​Mount Halimun Salak National Park (TNGHS) contains a diversity of insects with different ecological roles. In each type of habitat there was a composition of insect ecological roles. The study aimed to determine the diversity of ecological roles of insects in forest and plantation vegetation types in the Citalahab Area of ​​the Mount Halimun Salak National Park (TNGHS). This research uses the Simple Random Sampling method using pitfall traps in randomly determined plots measuring 20 x 20 meters (5 pit fall traps) in forests and plantations, with a total of 2 plots. There were 8 orders, 36 families with ecological roles such as: disease vectors, saprophages, pollinators, pests, predators, parasitoids, fungus eaters and decomposers. Insect families that act as parasitoids and disease vectors were only found in forest vegetation types. The richness of resources found in a habitat influences the diversity of the ecological roles of the insects found in it.